The role of I. V. Stalin in the history of architecture - Александр Раппапорт (Проект Байкал, 2021)
We have long regarded beating babies of avant-garde to be the most serious cultural crime, which threw the USSR back from the front line of architecture by 20-30 years and made them start from the beginning in 1960. If Stalin had seen a mainstream for architecture in that advanced idea and supported it, we would have had quite a different Soviet architecture today. His choice put an end to the constructivism utopia, according to which architecture would become a technical means of life organization. Ginzburg’s constructivism of the 1920s was a clear program of the common style and environmental standard, which could make an oppressive impression in the hands of third-rate doers. Unrealized opportunities of constructivism now don’t look so desirable. The paradoxicality of choosing academism and Stalin’s Empire style has probably another logic, a logic of reflexive frauds and false pretenses. However, if constructivism had remained as a general line for about 30 years, we would have had a kind of culture resembling Orwell more than anything else.